Prevention of Esophageal Stricture After Whole Circumferential Endoscopic Resection: A Review for Endoscopists - Zou, Jiale; Chai, Ningli; Linghu, Enqiang; Wang, Zantao; Li, Longsong (Turkish Journal of Gastroenterology, 2022)
The incidence of esophageal stricture without stricture prophylaxis measures after whole circumferential endoscopic resection is almost 100%, which substantially decreases the patients’ quality of life and requires multiple sessions of endoscopic balloon dilation. To date, there are many reports concerning the prevention of esophageal stricture after whole circumferential endoscopic resection. Oral steroid may be effective for preventing esophageal stricture after whole circumferential endoscopic resection. However, exposure to a high dose of steroid raises concerns with regard to adverse events. Intralesional triamcinolone acetonide injection and preventive endoscopic balloon dilation did not appear to reduce the frequency of stricture formation after whole circumferential endoscopic resection. Esophageal stent appeared to be a possible prophylactic treatment, but adverse events should be of great concern. Polyglycolic acid sheets seemed promising, because they can not only act as protective barriers but can also be drug carriers to prevent esophageal stricture. Tissue engineering and regenerative medicine such as oral mucosal epithelial cell sheets cultured in vitro have been used in patients to prevent esophageal stricture, but it is technically and financially burdensome. Autologous tissue transplantation showed a promising preventive effect for esophageal stricture and it is relatively easy to carry out in clinical practice, and this technique needs further improvements to prevent esophageal stricture after whole circumferential endoscopic resection. Cite this article as: Zou J, Chai N, Linghu E, Wang Z, Li L. Prevention of esophageal stricture after whole circumferential endoscopic resection: A review for endoscopists. Turk J Gastroenterol. 2022;33(10):811-821.